Myasthenia Gravis in Patients with Histopathologically Diagnosed Thymoma at Sanglah General Hospital: A Case Series - Desak Putu Gayatri Saraswati Seputra; I Gusti Ayu Sri Mahendra Dewi (Indonesian Journal of Cancer, 2021)
Introduction: Thymoma is a neoplasm of the thymus gland which arises from the epithelial tissue. Thymoma is frequently related to various paraneoplastic syndromes, most commonly myasthenia gravis. Up to 50% of patients with thymoma are reported to develop myasthenia gravis, whereas 10–15% of patients with myasthenia gravis are found to have thymoma. Case Presentation: This case series reported 3 patients with myasthenia gravis which co-occurred with thymoma at Sanglah General Hospital from 2018 to 2019. The patients’ ages range from 33 to 61 years (mean age 46 ± 11 years) with a 2:1 male-to-female ratio. The diagnosis of myasthenia gravis was made by the presentation of typical myasthenia gravis appearances, the fluctuating intensity of ocular and bulbar muscle weakness (all three cases), and limbs and axial muscle weakness (one case); no respiratory muscle involvement was found. Physical and supporting examinations including electroneuromyography results were coherent with myasthenia gravis. The diagnosis of thymoma was made by highly suggestive appearance in Thorax Multi Sliced Computed Tomography (MSCT) scan examination and histopathologic findings. MSCT scan examination showed a well-circumscribed ovoid solid mass in the mediastinum (left anterosuperior, superior, and anterior to middle right mediastinum) sized from 1.8x1.5x2.9 cm to 8.1x9.9x9.7 cm, enhanced with contrast injection with areas of calcification and central necrotic (1 case) and no dissemination to regional lymph node and neighboring organs. All cases received acetylcholinesterase inhibitors and underwent extended thymectomy. Histopathological examination showed accordance with thymoma features of subtype A, AB, and B1.Conclusions: Clinicians should be aware of the thymoma and myasthenia gravis co-existence possibility to ensure early recognition and appropriate management.